2022
DOI: 10.3390/biology11030359
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoporotic Effect of Lactobacillus brevis AR281 in an Ovariectomized Mouse Model Mediated by Inhibition of Osteoclast Differentiation

Abstract: Osteoporosis is a global disease characterized by weakened bone microarchitecture, leading to osteoporotic fractures. Estrogen replacement therapy is the traditional treatment for osteoporosis but carries with it an increased risk of cardiac events. In search of a safe and effective treatment, we used Lactobacillus brevis AR281, which has anti-inflammatory properties, to conduct a 7-week experiment, investigating its inhibitory effects on osteoporosis in an ovariectomized (ovx) mouse model. The results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…To further investigate the effect of probiotic treatment on bone formation, we examined the data from twenty-two selected articles that reported serum bone formation markers levels. Of these, six studies reported on serum osteocalcin (16,25,31,33,34,42) , seven studies on serum Ca (16,25,27,30,31,41,42) and six studies on serum ALP (27,29,30,34,40,41) . Pooled effect analysis was carried out using random effects model due to sufficient heterogeneity among studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further investigate the effect of probiotic treatment on bone formation, we examined the data from twenty-two selected articles that reported serum bone formation markers levels. Of these, six studies reported on serum osteocalcin (16,25,31,33,34,42) , seven studies on serum Ca (16,25,27,30,31,41,42) and six studies on serum ALP (27,29,30,34,40,41) . Pooled effect analysis was carried out using random effects model due to sufficient heterogeneity among studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to high heterogeneity, meta-analysis could not be performed on Bifidobacterium . Similarly, serum ALP was reported in six articles using Lactobacillus (27,29,30,34,40,41) and only one article using Bifidobacterium (30) , preventing a comparison of the two species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Many benecial effects including antioxidant, antimicrobial, anti-inammatory, antiviral, immunomodulatory, antitumor, and cholesterol adsorption activities of LAB-derived EPSs have been reported. 3,5,6 Furthermore, LAB-derived EPSs are used as syneresis-lowering agents, texturizers, viscosiers, and emulsi-ers, and also exhibited lm-making capabilities and pseudoplastic rheological behavior in the food industry. 7 Literature indicates that there are a number of factors such as carbon and nitrogen sources, pH of the culture media, growth medium, incubation temperature, enzyme production, and process conditions that affect the EPS production from LAB.…”
Section: Introductionmentioning
confidence: 99%
“…4 Many beneficial effects including antioxidant, antimicrobial, anti-inflammatory, antiviral, immunomodulatory, antitumor, and cholesterol adsorption activities of LAB-derived EPSs have been reported. 3,5,6 Furthermore, LAB-derived EPSs are used as syneresis-lowering agents, texturizers, viscosifiers, and emulsifiers, and also exhibited film-making capabilities and pseudoplastic rheological behavior in the food industry. 7…”
Section: Introductionmentioning
confidence: 99%